A growth mindset can boost support for increasing the minimum wage - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2023)
In the U.S., the value of the federal minimum wage has declined to record lows due to rising inflation. Recent research sheds light on a new factor that may contribute to people’s opinions for or against raising the minimum wage: a growth vs. fixed mindset. The authors hypothesized that decision-makers’ mindsets about intelligence — specifically the belief that abilities are stable (i.e., a fixed mindset) rather than the belief that abilities can grow and develop over time (i.e., a growth mindset) — might contribute to people’s opposition to increasing low-wage workers’ compensation. This held true in correlational and experimental studies, and this pattern held among those who identified as “liberal” or “conservative,” as well as across the social class and income spectrum. While mindsets are just one of the many systemic and psychological factors that contribute to support for or against raising the minimum wage, these findings suggest that grassroots advocates, managers, and business and political leaders seeking support for increasing low-wage workers’ wages may want to consider invoking the growth mindset about intelligence.